2014
DOI: 10.1002/eco.1583
|View full text |Cite
|
Sign up to set email alerts
|

Changes in evapotranspiration and phenology as consequences of shrub removal in dry forests of central Argentina

Abstract: More than half of the dry woodlands (forests and shrublands) of the world are in South America, mainly in Brazil and Argentina, where in the last years intense land use changes have occurred. This study evaluated how the transition from woody‐dominated to grass‐dominated system affected key ecohydrological variables and biophysical processes over 20 000 ha of dry forest in central Argentina. We used a simplified surface energy balance model together with moderate‐resolution imaging spectroradiometer–normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
(74 reference statements)
1
13
0
6
Order By: Relevance
“…A few studies have evaluated the ecohydrological impact of dry forest clearance and cultivation in South America (Amdan, Aragón, Jobbágy, Volante, & Paruelo, 2013;Jayawickreme, Santoni, Kim, Jobbágy, & Jackson, 2011;Santoni, Jobbágy, & Contreras, 2010), being confined to specific study areas. For example, a study in dry forests of central Argentina indicated that the elimination of perennial woody vegetation with deep root system and longer active phenology shortened the growing season by 3 months and reduced evapotranspiration by 30% (Marchesini, Fernández, Reynolds, Sobrino, & Di Bella, 2015).…”
Section: Land Use Changes In the Dry Forests Of South Americamentioning
confidence: 99%
“…A few studies have evaluated the ecohydrological impact of dry forest clearance and cultivation in South America (Amdan, Aragón, Jobbágy, Volante, & Paruelo, 2013;Jayawickreme, Santoni, Kim, Jobbágy, & Jackson, 2011;Santoni, Jobbágy, & Contreras, 2010), being confined to specific study areas. For example, a study in dry forests of central Argentina indicated that the elimination of perennial woody vegetation with deep root system and longer active phenology shortened the growing season by 3 months and reduced evapotranspiration by 30% (Marchesini, Fernández, Reynolds, Sobrino, & Di Bella, 2015).…”
Section: Land Use Changes In the Dry Forests Of South Americamentioning
confidence: 99%
“…Although rainfed agriculture is not usually profitable in our study site, there is room for improving forage production for extensive cattle raising. Our results, and some experiences from local farmers, highlight the underlying litter effects that would potentially explain the effectiveness of the roller chopping practice based on favouring those key species that produce a large quantity (amount) of litter, such as Prosopis flexuosa trees (Blanco et al, 2005;Marchesini et al, 2015;Steinaker et al, 2016). This study suggests that the conditions generated by the roller-chopping practice (open canopies and large amount of palatable grasses) in combination with the ecohydrological effect of high amounts of litter on surface are the key to improve extensive livestock production in Dry Chaco rangelands.…”
Section: Resultsmentioning
confidence: 65%
“…Under practical conditions, reference evapotranspiration, rainfall inputs, and soil type are not controllable factors, but the amount, distribution, and persistence of litter (or crop residues in agricultural systems) are amenable to be controlled by management practices (Klocke et al, 2009;Steiner, 1989;Van Donk et al, 2010). Our results, and some experiences from local farmers, highlight the underlying litter effects that would potentially explain the effectiveness of the roller chopping practice based on favouring those key species that produce a large quantity (amount) of litter, such as Prosopis flexuosa trees (Blanco et al, 2005;Marchesini et al, 2015;Steinaker et al, 2016). 500-600 mm/year) such as the southern great plains in United States or the northeast plain in China (Ji & Unger, 2001).…”
Section: Figurementioning
confidence: 73%
See 1 more Smart Citation
“…It is unclear how long complete recovery will take, but the timing may be similar to recovery from other disturbances. For example, after repeated vehicle damage, L. tridentata experienced no mortality and canopy size recovered within five years (Gibson, Sharifi, & Rundel, 2004), and following roller-chopping, productivity of the related species Larrea divaricata recovered to pretreatment levels in four years (Marchesini, Fernández, Reynolds, Sobrino, & Di Bella, 2015). Resprouting patterns of L. tridentata are also linked to disturbance severity (Bellingham & Sparrow, 2000).…”
Section: Discussionmentioning
confidence: 99%